KONTRAK PEGADAIAN BARANG DAN JASA DI DINAS PEKERJAAN UMUM KABUPATEN BREBES DITINJAU DARI PRESPEKTIF KENOTARIATAN - Rizqi Iman Aulia Luqmanul Hakim; Maryanto Maryanto (Jurnal Akta, 2017)
The Goods and Services Procurement Agreement is a complex agreement because it regulates many aspects both legally and technically about the procurement process of goods and services, requiring further study in order to find the ideal contract format for procurement of goods and services in accordance with the needs and able to provide protection and certainty law for the parties that make it.The problems in this research are: 1) How is the legal force of the government procurement contract made under the hands? 2) How is Notary's role in making government procurement contracts? 3) How is the legal protection of the parties in the event of breach of contract (wanprestasi) that harms the State?Approach method used in this research is normative juridical approach method, this research specification is analytical descriptive, data source that is primary and secondary data, data collecting method use by library study, method of data analysis with qualitative analysis.Result of research: 1) Agreement under the hand signed by the parties concerned. Such an agreement is only binding on the parties to the treaty but has no binding power to a third party. 2) Notary's role in the manufacture of Government Procurement of Goods and Services Contract in the form of an authentic deed, According to Article 1 paragraph 1 of Law Number 2 Year 2014 Notary Public Notary: Public Notary is authorized to make authentic deeds and other powers as referred to in the Act, 3) The protection of the law shall be initiated by the obligation of the parties to enter into a procurement agreement of goods and services by containing the clauses already stipulated as one of the legal protection measures for the parties, in the charter agreement.Suggestions in this research is Need a good coordination between the assignor, contractor, planner and supervisor in the implementation pemborongan building. With good coordination, the implementation of building projects can be implemented efficiently, effectively and planned. Keywords: Contract, Goods And Services From, Notary's Perspective